2012
DOI: 10.1016/j.ijrobp.2011.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tumor Subtype on Survival and the Graded Prognostic Assessment for Patients With Breast Cancer and Brain Metastases

Abstract: BACKGROUND The diagnosis-specific Graded Prognostic Assessment (GPA) was published to clarify prognosis for patients with brain metastases. This study refines the existing Breast-GPA by analyzing a larger cohort and tumor subtype. METHODS A multi-institutional retrospective database of 400 breast cancer patients treated for newly-diagnosed brain metastases was generated. Prognostic factors significant for survival were analyzed by multivariate Cox regression (MCR) and recursive partitioning analysis (RPA). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
208
6
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(234 citation statements)
references
References 49 publications
12
208
6
8
Order By: Relevance
“…In our analysis, the only variable that approached significance was breast cancer histological type, and although only 14% of all other patients survived longer than 1 year, > 40% of patients with metastatic breast cancer survived more than 1 year. Sperduto et al 21 reported on risk grouping among women with breast cancer and brain metastases that was based on hormone receptor status as well as Her2-neu and predicted median survival between 9.1 and 26.8 months. Our cohort is too small for such an analysis, however, and although these criteria were developed for patients with newly diagnosed brain metastases, they may be helpful for predicting survival in patients with multiple recurrent brain metastases as well.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the only variable that approached significance was breast cancer histological type, and although only 14% of all other patients survived longer than 1 year, > 40% of patients with metastatic breast cancer survived more than 1 year. Sperduto et al 21 reported on risk grouping among women with breast cancer and brain metastases that was based on hormone receptor status as well as Her2-neu and predicted median survival between 9.1 and 26.8 months. Our cohort is too small for such an analysis, however, and although these criteria were developed for patients with newly diagnosed brain metastases, they may be helpful for predicting survival in patients with multiple recurrent brain metastases as well.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of brain metastasis is high for patients who (1) are young, (2) have lymph node-positive disease and/or other systemic metastases, (3) are diagnosed with "triple-negative" breast cancer (ER-, PR-, HER2 unamplified), and/or whose tumors (4) overexpress HER2 [13,14]. In patients with the HER2-positive metastatic breast cancer, the frequency of brain metastasis has been reported to be as high as 50 % [15]. Brain metastases have emerged as a major challenge affecting morbidity and mortality of patients with HER2-positive metastatic breast cancer [16].…”
Section: Brain Metastases Of Breast Cancermentioning
confidence: 99%
“…При этом более половины больных HER-2 + РМЖ с метастазами в ГМ живут относительно долго [12]. Метастазирование в ГМ у пациентов с РМЖ является катастрофическим событием, предсказывающим пло-хой прогноз; медиана выживаемости, несмотря на ле-чение, колеблется от 2 до 25,3 мес [13,14]. Кроме того, метастазы данной локализации являются основной причиной прогрессирующих неврологических рас-стройств, приводящих к снижению качества жизни [15].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified